Ni Mg mixed metal oxides for p-type dye-sensitized solar cells - Zannotti, Marco; Wood, Christopher J.; Summers, Gareth H.; Stevens, Lee A.; Hall, Matthew R.; Snape, Colin E.; Giovannetti, Rita; Gibson, Elizabeth A. (American Chemical Society, 2015)
Mg Ni mixed metal oxide photocathodes have been prepared by a mixed NiCl2/MgCl2 sol-gel process. The MgO/NiO electrodes have been extensively characterized using physical and electrochemical methods. Dye-sensitized solar cells have been prepared from these films and the higher concentrations of MgO improved the photovoltage of these devices, however, there was a notable drop in photocurrent with increasing Mg2+. Charge extraction and XPS experiments revealed that the cause of this was a positive shift in the energy of the valence band which decreased the driving force for electron transfer from the NiO film to the dye and therefore the photocurrent. In addition, increasing concentrations of MgO increases the volume of pores between 0.500 to 0.050 μm, while reducing pore volumes in the mesopore range (less than 0.050 μm) and lowering BET surface area from approximately 41 down to 30 m2 g-1. A MgO concentration of 5% was found to strike a balance between the increased photovoltage and decreased photocurrent, possessing a BET surface area of 35 m2 g-1 and a large pore volume in both the meso and macropore range, which lead to a higher overall power conversion efficiency than NiO alone.